Tinjauan Yuridis Pelepasan Terdakwa dari Segala Tuntutan Hukum Dalam Kasus Tindak Pidana Penipuan Menurut Perspedktif Hukum Positif dan Hukum Islam: - Nahda Hasibuan; Budi Sastra Panjaitan; Annisa Sativa (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Fraud is someone's act of deception, a series of lies, false names and false circumstances with the intention of benefiting oneself without rights, a series of lies is an arrangement of false sentences arranged in such a way that is a story of something that seems to be true. The problem raised in this study is a case of criminal fraud which was processed before the court and then decided regardless of all lawsuits by the panel of judges. Based on this, the author raises issues related to how the provisions and basic considerations of the Medan District Court judge Number 1772/Pid.B/2021/PN.Mdn released the defendant from all lawsuits in the criminal case of fraud and the views of Islamic criminal law on criminal acts fraud crime. In this study the authors used normative legal research methods. The purpose of this study was to find out the provisions of positive law and Islamic criminal law against criminal acts of fraud, and the basis for the judges' considerations at the Medan District Court in case Number 1772/Pid.B/2021/PN.Mdn to release the defendant from all lawsuits in the criminal case fraud. In this case it can be concluded that the crime of fraud in positive criminal law and Islamic criminal law is an act that is forbidden to do (haram), the punishment for the crime of fraud is in the Criminal Code Article 378; Sanctions according to Islamic Criminal Law for criminal acts of fraud are subject to Ta'zir sanctions, and the basis for the judge's considerations in imposing an acquittal decision in this case is because it does not fulfill the elements of a criminal act of fraud. Keywords: Fraud; Islamic criminal law; Medan district court decision number 1772/Pid.B/2021/PN.Mdn.